Presence of pleural plaques and/or asbestosis and the risk of lung cancer in a crocidolite asbestos exposed population from Western Australia - Brims, Fraser; Musk, B.; Reid, A.; Pang, S.; Franklin, P.; Peters, S.; De Klerk, N. (2016)
Introduction/Aim: Asbestos exposure is associated with dose-dependent risk of benign pleural disease, lung cancer and mesothelioma. While an association between asbestosis and lung cancer (even after adjustment for asbestos exposure) is well established, the link between lung cancer and the presence of pleural plaque remains controversial with a recent report recent report containing small numbers of lung cancers (from death certificates) reporting an association. Methods: We followed 2218 subjects exposed to crocidolite asbestos as miners (n  = 1286) or mine township residents, monitored with annual review, chest radiography (CXR) and outcome linkage to national cancer and mortality registry data over a 25-year period. Subjects were followed up from the date of their latest X-ray taken a year or more before the date of death, cancer incidence or end of follow-up. Hazard ratios for lung cancer were estimated by Cox regression, with age as the underlying matching time variable, for sex, tobacco smoking, asbestos exposure estimates (time since first exposure and fibre/mL years), International Labour Organisation CXR readings for asbestosis (defined as profusion score > 1/0) and presence (and extent) of pleural plaques.Results: Mean age at follow-up was 60.6 years; 1575 (71%) were male; 328 (14.8%) had any pleural plaque, and 359 (16.2%) had asbestosis. One hundred three (4.64%) lung cancers were recorded. One thousand five hundred sixty-eight (70.7%) were ever-smokers with a mean tobacco exposure of 39.3 pack years. Hazard ratios are presented in Table 1.Conclusions: In our population, the presence of pleural plaque is not associated with an increased risk of subsequent lung cancer. As we have demonstrated previously, the presence of asbestosis and cumulative asbestos exposure both contribute to increased subsequent lung cancer risk, although previous tobacco smoke exposure remains the strongest risk factor.